Oral lichen planus has a very low malignant transformation rate: A systematic review and meta‐analysis using strict diagnostic and inclusion criteria. (8th February 2020) - Idrees, Majdy; Kujan, Omar; Shearston, Kate; Farah, Camile S.
Abstract: Background: The malignant transformation (MT) potential of oral lichen planus (OLP) has sparked heated debates for almost a century, despite the fact that global figures of OLP prevalence and oral cancer incidence do not support an association mathematically. In this study, we performed a systematic review and meta‐analysis, using strict inclusion criteria, to more precisely assess the malignant potential rate of OLP and the influence of associated risk factors. Methods: All reports that documented MT of OLP and published in the English language until January 2020 were included if they met the following strict criteria: (a) the presence of a properly verified OLP diagnosis, (b) a clear description of the cancerous lesion developing at the same site as the verified OLP lesion; and (c) a follow‐up period of a minimum of 6 months prior to carcinoma development. Results: Thirty‐three studies were included in this analysis with a total of 12 838 OLP patients. Of these, 151 cases were initially considered to have progressed to carcinoma (1.2%). However, after applying strict criteria, only 56 cases were considered to have undergone MT from OLP (0.44%). The risk of MT was significantly higher among OLP patients who smoked (OR = 4.62), consumed alcohol (OR = 3.22), were seropositive for HCV (OR = 3.77) and/or displayed a red OLP subtype (OR = 0.37). Conclusions: Our results suggest that the reported OLP malignant transformation rates are exaggerated, and these do not reflect the actual clinical course of the disease according to strict clinical and histopathological criteria.